Factors influencing the cytotoxicity of α-methylene-γ-hydroxy esters against pancreatic cancer. Issue 19 (1st October 2015) - Ramachandran, P. Veeraraghavan; Helppi, Matthew A.; Lehmkuhler, Arlie L.; Marchi, Jennifer M.; Schmidt, C. Max; Yip-Schneider, Michele T.
Graphical abstract: Abstract: A systematic study to identify the factors influencing the cytotoxicity of α-methylene-γ-hydroxy esters against three pancreatic cancer cell lines (Panc-1, MIA-PaCa-2, and BxPC-3) has established that, in addition to Michael acceptor abilities, the possibility to lactonize to α-methylene-γ-butyrolactones is as important. The substitution pattern and the number of carbons between the hydroxy and ester moieties also influence the bio-activity.